PENGARUH PENGETAHUAN KEUANGAN DAN PENGALAMAN KEUANGAN TERHADAP PERILAKU PERENCANAAN INVESTASI DENGAN SELF CONTROL SEBAGAI VARIABEL MODERATING - Untung Sriwidodo, Ritma Pritazahara (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
The purpose of this research are: 1) to analyze the significance of the effect of financial knowledge, experience and self-control of the financial investment planning on employee behavior single (unmarried) in the District Gondangrejo Karanganyar. 2) to analyze the moderating effect of self-control on the influence of financial knowledge and financial experience to the planning of investment in employee behavior single (unmarried) in the District Gondangrejo Karanganyar. In conclusion: There was a significant effect of financial literacy, financial experience and self-control on the behavior of the employee investment plan single (unmarried) in the District Gondangrejo Karanganyar. Self control is not moderate the effect of financial knowledge and financial experience to the planning of investment in employee behavior single (unmarried) in the District Gondangrejo Karanganyar. Keywords: financial literacy, financial experience, self-control and behavior of investment planning